Exploration of magnetically separable Ag@AgxNiy core/graded-alloy-shell nanostructures - Kumar, Mukesh; Soni, Kiran; Satpati, Biswarup; Gopinath, Chinnakonda S.; Deka, Sasanka (Chemical Communications, 2016)
We report novel bimetallic Ag@AgxNiy core@graded-alloy-shell nanoparticles (CGAS NPs), i.e. single Ag core NPs shelled by an AgxNiy graded alloy and stabilized by the CTAB surfactant employing a novel synthesis method. These Ag@AgxNiy CGAS NPs demonstrated superior catalytic performance in the synthesis of biologically active 3-amino alkylated indoles under green conditions.

Deposition of Au nanoparticles inside porous CeO2 nanocubes using Langmuir-Blodgett technique - Das, Subhasis; Bhattacharjee, Gourab; Satpati, Biswarup; Kumar, Mukesh; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal of Chemistry, 2018)
Porous 3D CeO2 nanocubes were synthesized using hot injection technique. These nanocubes were able to form a stable monolayer over water and HAuCl4 subphase in Langmuir-Blodgett (LB) trough due to the presence of surface capped oleic acid and oleylamine. CeO2-Au nanocomposites were synthesized exploiting the ability of oleylamine to reduce AuCl4 ions to Au-0, via LB method. CeO2 nanocubes gave rise to excellent long-range assembly at air/water interface and gold nanoparticles were formed inside these porous nanocubes without disturbing this arrangement. The formation of a stable monolayer was evidenced from the surface pressure-area (P-A) isotherm. The development of Au nanoparticles was confirmed with great effort from a comprehensive study using UV-Vis spectroscopy, XRD, XPS, FTIR, TEM, STEM, EDX, tomography and chemical mapping.

Functionalization of alkynes and alkenes using a cascade reaction approach: synthesis of beta-keto sulfones under metal-free conditions - Kumar, Mukesh; Ahmed, Riyaz; Singh, Maninder; Sharma, Shweta; Thatikonda, Thanusha; Singh, Parvinder Pal (Journal of Organic Chemistry, 2020)
Here, we are reporting a multicomponent cascade reaction approach for the synthesis of beta-keto sulfones by exploiting differential reactivity pattern of substrates under open-atmosphere and metal-free conditions. The coupling partners are aryldiazonium salts, unsaturated compounds, and DABSO. The optimized conditions worked well with both alkenes and alkynes. Moreover, the reaction also works with metabisulfite for the source of sulfone. The controlled liquid chromatography-mass spectrometry and O-18-labelled experiments suggested that air is a source of the incoming oxygen atom of the keto group of beta-keto sulfones.